PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PT. JASA MARGA PERSERO, TBK CABANG BELMERA - Winar Jelita Gulo; Yahya Tanjung (Jurnal Ilmu Manajemen METHONOMIX, 2020)
Leadership and motivation are factors that can affect employee performance. In this case, the leadership and motivation at PT Jasa Marga Persero, Tbk. Belmera Branch are classified as good and have an effect on employee performance. This study uses primary data where data is collected using a questionnaire. This research was conducted on employees at PT Jasa Marga Persero Tbk Belmera Branch with a population of 165 employees with a sample of 117 respondents. The data collected were analyzed using multiple linear regression analysis with partial test hypothesis testing (t test) and simultaneous test (f test). The findings of this researcher show that (1) the influence of leadership on employee performance is positive and significant. (2) the influence of motivation on employee performance is positive and significant. (3) the influence of leadership and motivation on monkeys' performance is positive and significant. The conclusion of this research is that there is a partial and simultaneous influence of leadership and work motivation on employee performance.